Impactos de sistemas de manejo do cafeeiro sobre a matéria orgânica e atributos físicos do solo no Território do Caparaó ES - Guimarães, Gabriel Pinto (2012)
Research assessing the impact of different management systems of coffee is essential to determine the chemical and physical characteristics of the soil. Starting from the hypothesis that the major input of organic matter improves the physical and chemical